The ethics of testing and research of manufactured organs on brain-dead/recently deceased subjects. Issue 3 (28th September 2019) - Parent, Brendan; Gelb, Bruce; Latham, Stephen; Lewis, Ariane; Kimberly, Laura L; Caplan, Arthur L
Abstract : Over 115 000 people are waiting for life-saving organ transplants, of whom a small fraction will receive transplants and many others will die while waiting. Existing efforts to expand the number of available organs, including increasing the number of registered donors and procuring organs in uncontrolled environments, are crucial but unlikely to address the shortage in the near future and will not improve donor/recipient compatibility or organ quality. If successful, organ bioengineering can solve the shortage and improve functional outcomes. Studying manufactured organs in animal models has produced valuable data, but is not sufficient to understand viability in humans. Before risking manufactured organ experimentation in living humans, study of bioengineered organs in recently deceased humans would facilitate evaluation of the function of engineered tissues and the complex interactions between the host and the transplanted tissue. Although such studies do not pose risk to human subjects, they pose unique ethical challenges concerning the previous wishes of the deceased, rights of surviving family members, effective operation and fair distribution of medical services, and public transparency. This article investigates the ethical, legal and social considerations in performing engineered organ research on the recently deceased.